PENERAPAN PEMBELAJARAN BERBASIS MASALAH DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Siregar, Nur Fauziah (IAIN PADANGSIDIMPUAN, 2015)
This study aims to determine: (1) to increase mathematical problem solving ability of students through the application of problem-based learning, and (2) to increase active activity levels of students with problem-based learning. This type of research is a class action. Subjects in this study are students of cass VII-3 SMP Negeri 7 Padangsidimpuan. The instrument uses a form of problem-solving ability test descriptions and observation. The results show that in the first cycle has not show optimal results therefore it needs the second cycle. In the Â second cycle shows an increase in the problems solving ability of students. In the first cycle is 50% rising to 89% in the second cycle. The levers of active studentâ€™s activity based on the observation shows at each meeting including both categories. Based on these result, the researcher suggests that the problem-based learning can be an altervative for teachers of mathematics to be developed as one of the effective learning to improve studentsâ€™ mathematics problem solving ability and increasing the activity of active students.